Preparation method of nanostructure YSZ target material for EB-PVD
The nanostructured YSZ target for EB-PVD is prepared by using YSZ fine nanostructure raw materials and spray granulation technology, and the particle size adjustment and cold isostatic pressing process are used to solve the problem of low cracking and deposition efficiency of the target under high-energy electron beam bombardment, and the high toughness, strength and stability of the target are achieved.
Patent Information
- Application Number
- CN202411992511.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the preparation of EB-PVD coating, the target material is prone to cracking, droplet splashing and deposition efficiency under high-energy electron beam bombardment, and the material's thermal shock resistance and electron beam radiation cracking resistance are insufficient.
The nanostructured YSZ target is prepared by using YSZ fine nanostructured raw materials and combined with spray granulation technology, and the porosity and volume shrinkage of the target are regulated through particle size adjustment technology and cold isostatic pressing process.
It improves the toughness, strength and stability of the target material, reduces firing time, enhances stability during use, and solves the problems of low cracking and deposition efficiency.
Smart Images

Figure CN119638415A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a target material for EB-PVD coating, and in particular to a method for preparing a nanostructured YSZ target material for EB-PVD. Background Art
[0002] The materials used for EB-PVD (electron beam physical vapor deposition) coatings must exhibit excellent heat resistance, given that they are deposited in areas of components that are in direct contact with high-temperature gases. Specifically, these materials must have high melting points and high purity to ensure their stability in extreme temperature environments. In addition, these coating materials must have good adhesion to metal parts, not be peeled off by thermal cycles, not be corroded by gas components, and have low thermal conductivity to keep the temperature of metal parts as low as possible, thereby improving their durability.
[0003] During the preparation of EB-PVD coatings, when the target (ingot) placed in the crucible is bombarded by a high-energy electron beam, if the vapor deposition material does not have the adjustment performance, it is very easy to break due to thermal shock. If such a break occurs in the vapor deposition material, it will pose a significant obstacle to the preparation of the coating, causing the target to splash, crack, and even break under stress and uneven structure. In order to improve the thermal shock resistance of the target, it is necessary to adjust its porosity. At the same time, the target material must also have better resistance to electron beam irradiation cracking. However, when the target is made of large particles with a wide particle size distribution and poor shape uniformity, its microstructure is uneven. Therefore, when the target is melted by electron beam irradiation during vapor deposition, it is difficult to form a stable molten pool. At this time, the deposition efficiency is greatly reduced when the internal structure of the target is uneven. If the electron beam power is increased to increase the deposition rate, it often leads to problems such as melt scattering. During the electron beam irradiation process, the rapid sintering of the material and the presence of internal pores will accelerate the sintering process of the target during rapid heating, so that it cannot withstand the stress associated with sintering shrinkage and fracture, causing cracking. It is worth noting that cracks and pores have the function of absorbing thermal shock energy to a certain extent, which helps to improve the thermal shock resistance of the material. Therefore, by adjusting the microstructure of the internal material, its thermal shock resistance can be improved, thereby preventing stress-induced fracture. The sintered body is characterized in that its porosity is between 5% and 50%, and the pore volume ranges from 0.1 to 10 microns. In particular, pores in the range of 0.1 to 10 microns should account for more than 95% of the total pore volume. Too low a porosity (less than 5%) will be detrimental to thermal shock resistance, because local heating during electron beam irradiation will produce thermal stress, which may lead to fracture. On the contrary, too high a porosity (more than 50%) will reduce the mechanical strength of the sintered body and affect its operability. In addition, if the proportion of pores with a diameter of 0.1 to 10 microns is less than 90%, the thermal shock resistance of the sintered body will be insufficient, which is also undesirable. In the production process of vapor deposition materials, the green compacts usually need to undergo heat treatment. In order to improve the performance of the green compacts, it is recommended to carry out combustion treatment at 1100°C or higher. If the combustion temperature is low, the resulting vapor deposition material will undergo sintering and heating shrinkage during electron beam irradiation. This shrinkage will induce the generation of large-area stress, thereby increasing the risk of material cracking. Therefore, high-temperature combustion treatment helps to reduce sintering shrinkage during electron beam heating, thereby inhibiting the formation of cracks.
[0004] Nano-ceramic materials developed using nanotechnology have microstructures with grains, grain boundaries and their bonding all at the nanometer level (1 to 100nm). This feature significantly enhances the strength, toughness and superplasticity of the material, effectively making up for many defects of traditional engineering ceramics. At the same time, it has a profound impact on the key mechanical and thermal properties of the material, opening up a new world for the replacement application of engineering ceramics. Nano-ceramic powders, as nano-scale (0.1 to 100nm) metastable transitional substances between solids and molecules, have a unique change in the surface electronic structure and crystal structure during the ultra-fine process, thus showing a specific effect that cannot be matched by bulk materials.
[0005] Specifically, nanopowder materials exhibit the following outstanding properties: their particle size is extremely small, their specific surface area is large, and they have excellent chemical properties. These properties can significantly reduce the sintering temperature of the material, thereby achieving effective energy conservation; at the same time, it can make the composition structure of the ceramic material more dense and uniform, significantly improve the performance of the ceramic material, and enhance its reliability. In addition, by accurately controlling the composition and structure of the material from the structural level of the nanomaterial (1 to 100nm), it is conducive to fully exploring and exerting the potential advantages of ceramic materials. On the other hand, the particle size of ceramic powder has a decisive influence on the microstructure and macroscopic properties of ceramic materials. When the powder particles are evenly distributed, the shrinkage is consistent during the firing process, and the grains grow evenly, the reduction in particle size will directly lead to a reduction in defects, thereby improving the strength of the prepared material. This characteristic makes it possible for nanopowder materials to exhibit some unique properties that traditional large-particle materials cannot match. Summary of the invention
[0006] Based on the above reasons, the present invention provides a method for preparing a nanostructured YSZ target for EB-PVD. This method uses YSZ fine nanostructured raw materials and combines spray granulation technology to not only successfully retain the characteristics of the nanostructure, but also significantly improve the compressibility of the target. The target prepared by the nanostructured raw materials has the advantages of high strength, excellent toughness, stable internal structure, uniform pores, etc., which reduces the firing time of the target and improves the stability of the target during use.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a nanostructured YSZ target for EB-PVD comprises the following steps:
[0009] Step 1: Screen the nanostructured YSZ spherical powder according to the particle size, and mix the screened nanostructured YSZ spherical powders with different particle sizes according to the mass ratio to obtain nanostructured YSZ spherical mixed powders with different particle sizes, wherein:
[0010] The screening specifications are 50-150 mesh, 150-300 mesh, 300-400 mesh, and the mass ratio is 2-6:1-3:1-5, and is used according to the powder particle size distribution and different porosity requirements;
[0011] The nanostructured YSZ spherical powder is one of nanostructured Y2O3 stabilized ZrO2 powder, rare earth doped Y2O3 stabilized ZrO2 powder, and enhanced phase doped Y2O3 stabilized ZrO2 powder, the rare earth doping content is 1-20wt%, and the enhanced phase content is 1-20wt%;
[0012] The nanostructured YSZ spherical powder is prepared by spray granulation technology, and the specific preparation steps are as follows:
[0013] Step (1) Adding zirconium oxide grinding balls and an appropriate amount of deionized water into a vertical ball mill, then adding a certain amount of dispersant, adding ultrafine nanostructured YSZ powder and milling for a period of time after the dispersant is completely dissolved, adding a certain amount of binder and continuing to mill for a period of time to obtain a uniform slurry, wherein:
[0014] The particle size of the ultrafine nanostructured YSZ powder is 5 to 90 nm;
[0015] The ultra-fine nanostructured YSZ powder raw material has a purity of 4N grade;
[0016] The ultrafine nanostructured YSZ powder is one of ultrafine grain structured Y2O3 stabilized ZrO2 powder, rare earth doped Y2O3 stabilized ZrO2 powder, and enhanced phase doped Y2O3 stabilized ZrO2 powder, the rare earth doping content is 1-20wt%, and the enhanced phase content is 1-20wt%;
[0017] The amount of deionized water used is 0.5 to 3 times the mass of the ultrafine nanostructured YSZ powder;
[0018] The dispersant is sodium tripolyphosphate (Na5P3O 10 ), sodium hexametaphosphate ((NaPO3)6), sodium pyrophosphate (Na4P2O7), ammonium citrate (C6H5O7(NH4)3), sodium citrate (C6H5Na3O7), polyvinyl alcohol (PVA), polyethylene glycol (PEG), etc. One or more of the dispersant, the amount of which is 0.03-6% of the mass of the ultrafine nanostructured YSZ powder;
[0019] The diameter of the zirconia grinding ball is 2 to 10 mm, the amount of the zirconia grinding ball is 1 to 5 times the mass of the ultra-fine nanostructured YSZ powder, the total ball milling time is 6 to 24 hours, and the number of revolutions is 300 to 1000 revolutions per minute;
[0020] The binder is one of gum arabic (Acacia), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), tetraethyl orthosilicate (TEOS), etc., and the amount of the binder is 0.1-10% of the mass of the ultra-fine nanostructured YSZ powder;
[0021] Step (2) The slurry obtained in step (1) is subjected to spray granulation to obtain micron-sized nanostructured spherical powder, and the powder is taken out and dried in an oven to obtain micron-sized nanostructured YSZ spherical powder, wherein:
[0022] The parameters of the spray granulation are as follows: the air inlet temperature is set at 200-250°C, the air outlet temperature is set at 100-130°C, the peristaltic pump speed is set at 30-45r / min, and the needle passing speed is set at 10-15t / min;
[0023] The drying temperature is 90-100°C and the drying time is 10-15h;
[0024] Step 2: adding deionized water to the YSZ spherical mixed powder obtained in step 1, then stirring the powder, and laying the aged powder flat to improve the molding performance to obtain aged powder, wherein:
[0025] The amount of deionized water added is 3-8% of the mass of the YSZ spherical mixed powder;
[0026] The aging time of the powder is 5 to 10 hours;
[0027] Step 3: Stir the aged powder obtained in step 2 evenly, put it into a sleeve, and press it using an upper and lower biaxial press. Put the green body after demoulding into a sealed bag and vacuum it, wherein:
[0028] The powder filling process uses ultrasonic vibration to improve density;
[0029] During the pressing process, the pressure is applied under upper and lower uniaxial pressure, the pressure is 20 to 50 MPa, and the pressure holding time is 10 to 30 minutes;
[0030] Step 4: The green body after vacuum sealing in step 3 is further pressed by cold isostatic pressing to obtain a target green body with different porosities, wherein:
[0031] During the pressing process, the pressure is controlled at 150-250 MPa, and the holding time is controlled at 120-300 s.
[0032] The cold isostatic pressing method can use wet bag cold isostatic pressing, dry bag cold isostatic pressing, press pre-pressing and other molding methods. Preferably, the cold isostatic pressing method is wet bag cold isostatic pressing;
[0033] Step 5: Sintering the target material green body obtained in step 4 to obtain nanostructured YSZ targets with different porosities, wherein:
[0034] The sintering mechanism is as follows: first, the temperature is raised to 350°C (debinding temperature) at a rate of 1 to 5°C / min and kept for 300 to 420 minutes, then, the temperature is raised to 800°C at a rate of 1 to 5°C / min and kept for 180 to 250 minutes, then, the temperature is raised to 1150 to 1300°C (synthesis temperature) at a rate of 1 to 5°C / min and kept for 120 to 360 minutes, then, the temperature is reduced to 600°C at a cooling rate of 1 to 5°C / min and kept for 120 to 150 minutes, and finally, the temperature is reduced to room temperature.
[0035] Compared with the prior art, the present invention has the following advantages:
[0036] 1. The present invention utilizes ultrafine nanostructured YSZ to prepare a nanostructured target suitable for electron beam physical vapor deposition, and provides a method for implementing the material on a thermal spray coating.
[0037] 2. The present invention is the first to use particle size adjustment technology and cold isostatic pressing process to prepare nanostructured target materials, which breaks through the problems of target materials being prone to cracking under high-energy electron beam bombardment, droplet splashing during the deposition process, and reduced deposition efficiency. The target materials prepared by the present invention have the advantages of high toughness, high strength, uniform internal structure, uniform pore distribution, wide range of material applications, easy operation, high deposition efficiency, and easy industrialization.
[0038] 3. The present invention utilizes particle size classification and mixing technology to press nanostructured spherical powder into a green embryo. In order to ensure that the overall volume shrinkage of the target material is minimized and has a certain porosity requirement, the target material sintering route is regulated to strictly control the porosity and volume shrinkage.
[0039] 4. The present invention solves the problem of cracking and poor thermal shock resistance when the target material is suddenly bombarded by a high-energy electron beam during use. The target material prepared by the present invention has high toughness at high temperature, excellent thermal shock resistance, stable internal structure, and has broad application prospects.
[0040] 5. The present invention can accurately control the volume shrinkage rate of the target material by controlling the sintering route and particle size grading technology, thereby solving the problems of unstable size of the target material after sintering and the need for subsequent turning processing, simplifying the target material preparation process and reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the structure diagram of YSZ raw material before spray granulation;
[0042] Figure 2 This is the structure diagram of YSZ spherical agglomerates after spray granulation;
[0043] Figure 3 The green target material after pressing;
[0044] Figure 4 This is the cross-sectional structure diagram of the target after sintering;
[0045] Figure 5 is the cross-sectional structure diagram of the target;
[0046] Figure 6 This is the pore distribution diagram. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0048] Embodiment 1:
[0049] This embodiment provides a method for preparing a nanostructured YSZ target for EB-PVD, the method comprising the following steps:
[0050] Step 1, ball milling the nanostructured YSZ powder to prepare a slurry: add zirconium oxide grinding balls and an appropriate amount of deionized water to a vertical ball mill, then add a certain amount of dispersant, add the nanostructured YSZ powder after the dispersant is completely dissolved, and then ball mill for a period of time, add a certain amount of binder and continue ball milling for a period of time to obtain a uniform slurry, wherein: the nanostructured YSZ powder is 4N grade purity and has a particle size of 20nm; the amount of deionized water is twice the mass of the nanostructured YSZ powder; the dispersant is sodium hexametaphosphate ((NaPO3)6, and the amount of the dispersant is 1% of the mass of the nanostructured YSZ powder; the diameter of the zirconium oxide grinding balls is 3mm and 5mm, the mass ratio is 6:4, the amount of the zirconium oxide grinding balls is twice the mass of the nanostructured YSZ powder, the ball milling time is 12h, the number of revolutions is 600 rpm; the binder is gum arabic (Acacia), and the amount of the binder is 3% of the mass of the nanostructured YSZ powder.
[0051] Step 2: The slurry obtained in step 1 is spray granulated to obtain micron-scale spherical powder, wherein: the air inlet temperature is 245°C, the air outlet temperature is 120°C, the needle passing frequency is 10 times per minute, and the peristaltic pump speed is 40 revolutions per minute; the powder is taken out and dried in an oven at 90°C for 12 hours to obtain nanostructured YSZ powder.
[0052] Step 3: The nanostructured YSZ powder obtained in step 2 is sieved with three specifications of 150 mesh, 200 mesh and 350 mesh, and the three specifications of powders are mixed in a mass ratio of 5:3:2 to obtain nanostructured YSZ mixed powder.
[0053] Step 4: Add 5% deionized water to the nanostructured YSZ mixed powder obtained in step 3, then stir the powder, and lay the powder flat for aging for 10 hours to improve the molding performance, thereby obtaining aged powder.
[0054] Step 5: Stir the aged powder obtained in step 4 evenly with a stainless steel spoon, put it into a stainless steel sleeve, and use an upper and lower biaxial press to press it. Ultrasonic vibration is used to improve the density during the powder filling process. Pressurize under upper and lower uniaxial pressure, control the pressure to 30 MPa, and hold the pressure for 10 minutes. Put the green body after demolding into a sealed bag and vacuum it.
[0055] Step 6: The green body after vacuum sealing in step 5 is further pressed by wet bag cold isostatic pressing method, the pressure is controlled at 200 MPa, and the holding time is controlled at 150 s to obtain a target green body.
[0056] Step seven, use a box-type sintering furnace to sinter the target material green embryo obtained in step six, and the sintering mechanism is: first, increase the temperature to 350°C (debinding temperature) at 2°C / min and keep it for 300min, then, increase the temperature to 800°C at 2°C / min and keep it for 180min, then, increase the temperature to 1200°C (synthesis temperature) at 2°C / min and keep it for 120min, then, reduce the temperature to 600°C at a cooling rate of 2°C / min and keep it for 180min, finally, reduce the temperature to room temperature to obtain a nanostructured YSZ target.
[0057] In this embodiment, the structure of the YSZ raw material before spray granulation is as follows: Figure 1 As shown in Figure 2, the structure of YSZ spherical aggregates after spray granulation is as follows: Figure 2 As shown in the figure, the spherical shape is good after spray granulation, and the spherical diameter distribution is uniform. Figure 3 As shown in the figure, the target material has a diameter of 80 mm and a height of 100 mm before sintering. The cross-sectional structure of the target material after sintering is as follows: Figure 4 As shown, the cross-sectional structure of the target is Figure 5 The pore distribution is shown in Figure 6 As shown. Figure 1 It can be seen that the original grains of YSZ raw material conform to the nanostructure; Figure 4 It can be seen that the grains of the nanostructured YSZ target are small and uniform, and the grain size distribution is between 100 and 500 nm. Figure 5 and Figure 6 It can be seen that the pore distribution of the nanostructured YSZ target is uniform, the pore size is uniform, and there are no obvious defects; the density and volume shrinkage of the target are shown in Table 1.
[0058] Table 1
[0059]
[0060] Embodiment 2:
[0061] This embodiment provides a method for preparing a nanostructured CeO2-doped YSZ target for EB-PVD, the method comprising the following steps:
[0062] Step 1: Mix the nanostructured YSZ powder and the nanostructured CeO2 and then perform ball milling to prepare a slurry: Add zirconium oxide grinding balls and an appropriate amount of deionized water to a vertical ball mill, then add a certain amount of dispersant, and after the dispersant is completely dissolved, add the nanostructured CeO2 and the nanostructured YSZ powder and perform ball milling for a period of time, then add a certain amount of binder and continue ball milling for a period of time to obtain a uniform slurry, wherein: the nanostructured YSZ powder is 4N grade purity and has a particle size of 5 to 90 nm; the nanostructured CeO2 powder is 4N grade purity and has a particle size of 2 0nm, the added amount is 3wt% of the mixed powder mass; the amount of deionized water is 3 times the mass of the mixed powder; the dispersant is sodium hexametaphosphate ((NaPO3)6, and the amount of the dispersant is 1.5% of the mass of the mixed powder; the diameters of the zirconia grinding balls are 3mm and 5mm, the mass ratio is 6:4, the amount of zirconia grinding balls is twice the mass of the nanostructured YSZ powder, the ball milling time is 12h, and the number of revolutions is 800 rpm; the binder is polyvinyl alcohol (PVA), and the amount of the binder is 1.5% of the mass of the mixed powder.
[0063] Step 2: The slurry obtained in step 1 is spray granulated to obtain micron-scale spherical powder, wherein: the air inlet temperature is 220°C, the air outlet temperature is 100°C, the needle passing frequency is 15 times per minute, and the peristaltic pump speed is 35 revolutions per minute; the powder is taken out and dried in an oven at 90°C for 12 hours to obtain CeO2-doped nanostructured YSZ agglomerated powder.
[0064] Step 3: The CeO2-doped nanostructured YSZ agglomerated powder obtained in step 2 is sieved with three specifications of 100 mesh, 200 mesh and 400 mesh, and the three specifications of powders are mixed in a mass ratio of 6:2:2 to obtain CeO2-doped nanostructured YSZ agglomerated mixed powder.
[0065] Step 4: Add 5% deionized water to the CeO2-doped nanostructured YSZ agglomerated mixed powder obtained in step 3, then stir the powder, lay the powder flat and age it for 6 hours to improve the molding performance, and obtain an aged powder.
[0066] Step 5: Stir the aged powder obtained in step 4 evenly with a stainless steel spoon, put it into a stainless steel sleeve, and use an upper and lower biaxial press to press it. Ultrasonic vibration is used to improve the density during the powder filling process. Pressurize under upper and lower uniaxial pressure, control the pressure to 30 MPa, and hold the pressure for 10 minutes. Put the green body after demolding into a sealed bag and vacuum it.
[0067] Step 6: The green body after vacuum sealing in step 5 is further pressed by wet bag cold isostatic pressing method, the pressure is controlled at 200 MPa, and the holding time is controlled at 150 s to obtain a target green body.
[0068] Step 7: Use a box-type sintering furnace to sinter the target green body obtained in step 6. The sintering mechanism is as follows: first, increase the temperature to 350°C (drying temperature) at 2°C / min and keep it for 300min, then increase the temperature to 800°C at 2°C / min and keep it for 250min, then increase the temperature to 1200°C (synthesis temperature) at 2°C / min and keep it for 360min, then decrease the temperature to 600°C at a cooling rate of 2°C / min and keep it for 120min, finally, decrease the temperature to room temperature to obtain a nanostructured CeO2 doped nanostructured YSZ agglomerated powder target. The density and volume shrinkage of the target are shown in Table 1.
Claims
1. A method for preparing a nanostructured YSZ target for EB-PVD, characterized in that The method comprises the following steps: Step 1, sieving the nanostructured YSZ spherical powder according to the particle size, and proportioning the sieving nanostructured YSZ spherical powders with different particle sizes according to the mass ratio to obtain nanostructured YSZ spherical mixed powders with different particle sizes, wherein: the sieving specifications are 50-150 mesh, 150-300 mesh, 300-400 mesh, the mass ratio is 2-6:1-3:1-5, and the powder is used according to the particle size distribution and different porosity requirements of the powder; Step 2: adding deionized water to the YSZ spherical mixed powder obtained in step 1, stirring the powder, and laying out the aged powder to improve the molding performance, thereby obtaining an aged powder; Step 3: Stir the aged powder obtained in step 2 evenly, put it into a sleeve, and press it using an upper and lower biaxial press. Put the green body after demoulding into a sealed bag and vacuum it; Step 4: further pressing the green body after vacuum sealing in step 3 by cold isostatic pressing to obtain target green bodies with different porosities; Step 5, sintering the target raw material obtained in step 4 to obtain a nanostructured YSZ target with different porosities, wherein: the sintering mechanism is: first, raising the temperature to 350°C at a rate of 1-5°C / min and keeping it for 300-420min, then, raising the temperature to 800°C at a rate of 1-5°C / min and keeping it for 180-250min, then, raising the temperature to 1150-1300°C at a rate of 1-5°C / min and keeping it for 120-360min, then, reducing the temperature to 600°C at a cooling rate of 1-5°C / min and keeping it for 120-150min, and finally, reducing the temperature to room temperature.
2. The method for preparing a nanostructured YSZ target for EB-PVD according to claim 1, characterized in that The nanostructured YSZ spherical powder is one of nanostructured Y2O3 stabilized ZrO2 powder, rare earth doped Y2O3 stabilized ZrO2 powder and enhanced phase doped Y2O3 stabilized ZrO2 powder, the rare earth doping content is 1-20wt%, and the enhanced phase content is 1-20wt%.
3. The method for preparing a nanostructured YSZ target for EB-PVD according to claim 1 or 2, characterized in that The nanostructured YSZ spherical powder is prepared by spray granulation technology, and the specific preparation steps are as follows: Step (1) adding zirconium oxide grinding balls and deionized water to a vertical ball mill, then adding a dispersant, adding ultrafine nanostructured YSZ powder after the dispersant is completely dissolved, and then ball milling for a period of time, and then adding a binder and continuing ball milling for a period of time to obtain a uniform slurry, wherein: the amount of deionized water is 0.5 to 3 times the mass of the ultrafine nanostructured YSZ powder, the amount of the dispersant is 0.03 to 6% of the mass of the ultrafine nanostructured YSZ powder, and the amount of the binder is 0.1 to 10% of the mass of the ultrafine nanostructured YSZ powder; Step (2) The slurry obtained in step (1) is subjected to spray granulation to obtain micron-sized nanostructured spherical powder, and the powder is taken out and dried in an oven to obtain micron-sized nanostructured YSZ spherical powder.
4. The method for preparing a nanostructured YSZ target for EB-PVD according to claim 3, characterized in that The dispersant is one or more of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, ammonium citrate, sodium citrate, polyvinyl alcohol, and polyethylene glycol; the diameter of the zirconium oxide grinding ball is 2 to 10 mm, the amount of the zirconium oxide grinding ball is 1 to 5 times the mass of the ultra-fine nanostructured YSZ powder, the total ball milling time is 6 to 24 hours, and the number of revolutions is 300 to 1000 revolutions per minute; and the binder is one of gum arabic, polyvinyl alcohol, carboxymethyl cellulose, and ethyl silicate.
5. The method for preparing a nanostructured YSZ target for EB-PVD according to claim 3, characterized in that The parameters of the spray granulation are as follows: the air inlet temperature is set at 200-250°C, the air outlet temperature is set at 100-130°C, the peristaltic pump speed is set at 30-45 r / min, and the needle passing speed is set at 10-15 t / min.
6. The method for preparing a nanostructured YSZ target for EB-PVD according to claim 3, characterized in that The drying temperature is 90-100° C., and the drying time is 10-15 hours.
7. The method for preparing a nanostructured YSZ target for EB-PVD according to claim 1, characterized in that The time for aging the powder is 5 to 10 hours.
8. The method for preparing a nanostructured YSZ target for EB-PVD according to claim 1, characterized in that When the upper and lower biaxial presses are used for pressing, the pressing is performed under upper and lower uniaxial pressures, the pressure is 20 to 50 MPa, and the pressure holding time is 10 to 30 minutes.
9. The method for preparing a nanostructured YSZ target for EB-PVD according to claim 1, characterized in that When the cold isostatic pressing method is used for pressing, the pressure is controlled at 150-250 MPa, and the holding time is controlled at 120-300 seconds.
10. The method for preparing a nanostructured YSZ target for EB-PVD according to claim 1 or 9, characterized in that The cold isostatic pressing method uses wet bag cold isostatic pressing, dry bag cold isostatic pressing, and press pre-pressing molding methods.
Citation Information
Patent Citations
Lanthanum zironate based ceramic target material for electron beam physical vapor deposition and preparation method thereof
CN107903060A
Thermal barrier coating powder applied to plasma physical vapor deposition and preparation method of thermal barrier coating powder
CN108103431A
Preparation method for high-uniformity, short-process ceramic target material for electron beam physical vapor deposition thermal barrier coating
CN108358648A
Preparation method of large-size zirconia ceramic target material for thermal barrier coating
CN109721356A
Nano mullite powder for plasma physical vapor deposition and preparation method of nano mullite powder
CN111534796A